Understanding Instructors’ Perspectives on Differentiated Education: Insight and Practical Approaches from a Comprehensive Literature Review - Vinola, Vinvin; Siregar, M. Riskiyadi; Eliwarti,; Hadriana,; Daud, Afrianto (Jurnal Paedagogy, 2026)
This study aims to analyze teachers’ perceptions and implementation of differentiated instruction (DI) and to identify the key barriers and implications for improving DI within the Indonesian education system. The study adopted a systematic review approach based on the PRISMA 2020 guidelines. Articles were retrieved from Scopus, Google Scholar, and Semantic Scholar using Boolean search operators. Of the 151 articles initially identified, 15 empirical studies published between 2022 and 2026 met the inclusion criteria. The selected studies were analyzed using thematic analysis. The findings indicate that Indonesian teachers generally hold positive perceptions of differentiated instruction, recognizing its potential to address learner diversity, enhance student engagement, and promote inclusive learning. However, the implementation of DI remains inconsistent and largely superficial. Although content differentiation is widely implemented, process differentiation, product differentiation, and systematic diagnostic assessment receive considerably less attention. Major barriers to effective implementation include limited instructional time, large class sizes, inadequate learning resources, insufficient diagnostic assessment literacy, limited professional development opportunities, and varying levels of teacher readiness. This study contributes to the literature by synthesizing recent empirical evidence on teachers’ perceptions and implementation of differentiated instruction in Indonesia and highlighting priority areas for policy, teacher professional development, and future research.